University Students and ChatGPT: Redefining Learning in the Age of Artificial Intelligence - Novita, Pipit; Yusof, Mat Rahimi; zaitun, zaitun (English Language in Focus (ELIF), 2024)
Artificial Intelligence (AI) has significantly reshaped the world of education, particularly in how university students access and interact with learning resources. Among the various AI tools, ChatGPT stands out for its capability to engage advanced, human-like conversations, offering students a novel way to obtain information and interact with academic content. This study aims to investigate university students' perspectives on using ChatGPT compared to traditional textbooks as learning resources. Employing a qualitative research design, semi-structured interviews were conducted with 12 students from Indonesia and Malaysia, allowing for a comparative analysis of their experiences. The findings reveal a significant paradigm shift in learning behaviours, with ChatGPT emerging as the preferred initial resource, even among students who recognize the importance of textbooks. This research highlights the transformative potential of AI in education and emphasizes the necessity for educators to adapt their teaching practices to effectively support student learning in an increasingly AI-driven environment.